(Ar–CO–CC)(PEt3)Au and (Ar–CC)(PEt3)Au complexes bearing pyrenyl and ferrocenyl groups: synthesis, structure, and luminescence properties. Issue 19 (27th April 2018) - Głodek, Marta; Makal, Anna; Paluch, Piotr; Kadziołka-Gaweł, Mariola; Kobayashi, Yasuhiro; Zakrzewski, Janusz; Plażuk, Damian
Abstract : ArCOCCAuPEt3 (1a and1b ) and ArCCCAuPEt3 (2a and2b ) bearing Ar = pyren-1-yl or ferrocenyl group were synthesized and the structure, ligand scrambling in solution and luminescence properties were investigated. Abstract : Two types of (acetylide)(triethylphosphine)gold(i ) complexes ArCOCCAuPEt3 (1a and1b ) and ArCCAuPEt3 (2a and2b ) bearing Ar = pyren-1-yl or ferrocenyl group were synthesized and the effect of a carbonyl moiety on the structure, propensity to ligand scrambling in solution and luminescence properties were investigated. We found that the complexes bearing acetylenic ketone-derived ligands underwent ligand scrambling in solution to afford mixtures of ArCOCCAuPEt3 and [(ArCOCC)2 Au] − [Au(PEt3 )2 ] + . The latter complexes were isolated and their structures were confirmed by single crystal X-ray diffraction studies. The aurophilic interaction of Au⋯Au in these complexes resulted in the formation of wire-like structures.